Financial Ratio Analysis in Assessing Financial Performance of Denpasar City Government for the Year 2018 – 2021 - Ida Ayu Putu Jyotisna Garbania; I Made Bagiada; I Made Agus Putrayasa (Journal of Applied Sciences in Accounting, Finance, and Tax, 2022)
The execution of the standard of decentralization with regards to understanding the local independence of city in the Province of Bali has not been completely ready to investigate provincial pay sources which will uphold the outcome of carrying out territorial independence. Monetary information written in the Regional Government Budget isn't adequate to give sufficient data with respect to monetary administration execution in a specific locale. This exploration looked to evaluate the presentation of territorial monetary administration in Denpasar City during 2018-2021, as estimated by the local monetary reliance proportion, adequacy proportion, productivity proportion, the provincial consumption similarity proportion, the level of financial decentralization proportion and development proportion. Monetary Ratio Analysis utilizing the Budget Realization Report can be an estimating instrument for evaluating the monetary exhibition of nearby government. The exploration results uncovered that the monetary administration execution of Denpasar City during 2018-2021 still generally low in a few proportions explicitly the territorial monetary reliance proportion, productivity proportion, the level of monetary decentralization proportion and development proportion, while viability pro- portion and the local consumption similarity proportion show great monetary execution. It tends to be seen from its low territorial independence and its high reliance on the focal government. Furthermore, the territorial government has not had the option to smooth out the local funds in which provincial consumptions were more prominent than provincial incomes. The development pace of provincial monetary administration can be sorted as bad, since there is a lessening in pay consistently during the estimation time of the financial year.